Biology of Anopheles gambiae and insecticide resistance: Entomological study for a large scale of indoor residual spraying in South East Benin - Padonou, G.G.; Sezonlin, M.; Gbedjissi, G.L.; Ayi, I.; Azondekon, R.; Djenontin, A.; Bio-Bangana, S.; Oussou, O.; Yadouleton, A.; Boakye, D.; Akogbeto, M. (My University, 2011)
Indoor residual spraying (IRS) has been proposed by the National Malaria Control Programme of Benin in the districts of Adjohoun, Dangbo, Misserete and Seme. Up to date entomological data are unavailable in these districts. To be effective, this measure must be based on the knowledge of biology of the malaria vectors. To achieve this aim, vector collections were made in the study area. A total of 49.059 Culicidae were captured. Anopheles gambiae s.s accounted for 20.91% while Anopheles funestus accounted for only 0.007%. An. gambiae s.s were molecular form M, resistant to DDT and permethrin, but susceptible to deltamethrin (mortality 100%) and bendiocarb (mortality 100%). Endophilic, blood feeding and endophagic rates were respectively estimated to be 65.74%, 53.23 and 70.18%. There was no seasonal variation of longevity, but the entomological inoculation rate ranged from 0 to 0.73 infective bites/ person / night according to localities and seasons. This study confirms a high spatial heterogeneity in mosquito distribution and shows that An. gambiae s.s is highly endophagic and endophilic (feed and rest indoor) in south east Benin. While the vector remains susceptible to deltamethrin, high levels of kdr suggest that the use of pyrethrinoid for IRS may be at risk.
Keywords: Anopheles gambiae; endophily; blood feeding; parturity; entomological inoculation rate; resistance; IRS; Benin